A public health approach for addressing recidivism and addiction using European concepts in Alaska. (20th October 2021) - Ray, R
Abstract: Problem: Criminal activity attributed to substance misuse is a tremendous challenge to public health and public safety. Over 80% of Alaska's incarcerated population has an addiction disorder. These individuals are 129 times more likely to die of a drug overdose within two weeks after reentry. Nearly 83% will likely be rearrested. This complex problem has a costly impact. In 2017, 25, 450 Alaskans were victims of crimes directly attributed to substance misuse for a total cost of over 2.3 billion. Description: The Alaska Recidivism Reduction and Recovery Project is a comprehensive intervention addressing the primary risk factors of ongoing criminal activity and substance misuse within an innovative therapeutic campus model and a mobile health platform. The intervention uses a conceptual framework derived from the European Union's Triple-R Model and the Norway Model of Restorative Justice. Living on a therapeutic campus for an average of 6-18 months, formerly incarcerated adults engage in a suite of services designed to transform criminogenic needs. Services also employ an innovative mobile health platform using Oracle's Intelligent Advisor technology. The project aims to increase access to critical community care, improve participants' quality of life, and improve public health and safety by reducing crime related to substance misuse. Results: Preliminary results suggest the intervention may significantly improve access to care upon reentry while creating meaningful changes in criminogenic needs. Early indications also suggest substantial cost savings may be achieved. For every 80 successful participants in Alaska, data suggests cost savings and net economic benefits may reach 20 million. Lessons: European concepts can be successfully replicated in Alaska to create an impactful intervention addressing criminal recidivism and addiction. Given the correlation between crime and addiction, this practice may provide a critical pathway for improving public health and safety. Key messages: European conceptual frameworks can be successfully replicated in Alaska to create a meaningful community-based intervention for reducing criminal recidivism and substance misuse. An innovative intervention in Alaska addressing the primary risk factors of criminal activity and substance misuse demonstrates the potential to achieve significant social impact and cost savings.